NILAI-NILAI MULTIKULTURAL DALAM KEHIDUPAN MAHASISWA DIFABEL DI UNIVERSITAS ISLAM NEGERI SUNAN KALIJAGA YOGYAKARTA - M. Ainul Yaqin (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
This article is the outcome of research that focuses on the study of thedevelopment and implementation of multicultural values and its effect to the social and academic life of diffables studens at UIN Sunan Kalijaga Yogyakarta. The object of this discourse is multicultural values and social and academic life of diffable students. Because civitas academica especially the students come from different cultural backround such as social class, ethnic, local language, age, ability and gender, developing and implementing multicultural values which are based on three moral principles such as humanism, social justice, and democracy become very important. The tentative summary of this research based article is the development and implementation of multicultural values give strong significant to the diffable students’ social and academic life in UIN Sunan Kalijaga Yogyakarta.Keywords: Mulicultural values, diffable, and islamic university